Co-pigmentation of Anthocyanin Jamblang Fruit (Syzygium cumini) with Acetic Acid and Alum - Chintia N. Barani; Siti Nuryanti; Paulus H. Abram (Jurnal Akademika Kimia, 2021)
This study aimed to determine the effect of temperature on the stability of anthocyanin jamblang after co-pigmentation with acetic acid and alum. The extraction of Jamblang fruit used the maceration method with n-hexane, ethyl acetate, and ethanol-HCl 0.5% solvents. The total anthocyanin obtained was 70.64 mg/L. Anthocyanin of jamblang fruit was co-pigmented with acetic acid and alum in a concentration of 2.5%; 5%; 7.5%; and 10%, then be heated at various temperatures and heating times. At a temperature of 80 ℃ for 150 minutes, every 30 minutes, absorbance was measured. At a temperature of 60 ℃, the heating was carried out for 225 minutes, and every 45 minutes, absorbance was measured. At a temperature of 40 ℃, the heating was carried out for 300 minutes, and every 60 minutes, absorbance was measured. Absorbance measurements were taken using a UV-VIS spectrophotometer. The results showed that co-pigmentation of anthocyanin occurred proved by shifting λ max from 470 nm (unco-pigmented extract) to 500 nm (co-pigmented extract acetic acid) and 540 nm (co-pigmented extract alum). Acetic acid and alum co-pigments maintained the stability of anthocyanin jamblang at a heating temperature of 60 ℃. It can be seen from decreased absorbance, which is not so significant compared to the decrease at temperatures of 40 and 80 ℃, accompanied by anthocyanin's fading color, which is co-pigmented with acetic acid and alum during the heating process.